TIPOLOGI NALAR MAYARAKAT TERHADAP LARANGAN PERKAWINAN ADAT KEBO BALIK KANDANG - Sella Dyah Ariska; Muhammad Solikhudin; Fatimatuz Zahro (Minhaj: Jurnal Ilmu Syariah, 2023)
Marriage is an inner and outer bond between a man and a woman who previously had not been halal to become halal with the aim of worshiping Allah SWT in order to form a happy family, sakinah, mawaddah wa rahmah, and the blessings of the world and the hereafter. However, in reality in Indonesia, there are many kinds of culture/customs. Especially in Java, there are many kinds of customs which for them are prohibitions that should not be violated. Such as the prohibition of traditional marriage of kebo balik kandang in Tanjungtani Village, Prambon District, Nganjuk Regency. The reality shows that the ban on traditional marriage of kebo balik kandang has become a matter of pros and cons for the people of Tanjungtani Village because in the community's view there are different views, including the views of classical, modern and religious leaders. he views of modern society are indifferent to the tradition, the views of classical society still believe in the tradition and religious leaders maintain control of harmony by respecting tradition and there is a dialectical process of customary law and Islamic law or maqasid al-shari'ah in particular. This is a social construction in Tanjungtani Village, Prambon District, Nganjuk Regency. With the existence of these different views because they are influenced by several factors, both cultural factors, educational factors, people's mindsets, and incident factors that make a form of experience with the existence of these experiences, some people in Tanjungtani Village believe in the prohibition of traditional marriage of kebo balik kandang.